Sagot :
Answer:
x_1 = 1/2 , x_2 = 1
Step-by-step explanation:
2x^2 - 3x + 1 =0
x^2 - (3/2)x + 1/2 = 0
next is let x_1 and x_2 be the roots of the equation
let x_1 = -b/2 - u and x_2 = -b/2 + u
it is known that
(x_1)(x_2) = c
if a=1
in ax^2 + bx + c = 0
then lets substitite with the values we let in
(-b/2 - u)(-b/2 + u) = c
(3/4 - u)(3/4 +u) = 1/2
9/16 - u^2 = 1/2
u^2 = 9/16 - 8/16
u = +/- 1/4
then find x_1 and x_2 with the values you got
x_1 = -b/2 - u
=(3/2)(1/2) - 1/4
=3/4 - 1/4
x_1=1/2
x_2 = -b/2 + u
=(3/2)(1/2) + 1/4
=3/4 + 1/4
x_2=1
then for x^2 + 2x - 3 = 0
with the form of ax^2 + bx + c = 0
Let x_1 = -b/2 - u , x_2 = -b/2 + u
it is known that
(x_1)(x_2) = c
then sub
(-b/2 - u)(-b/2 + u ) = c
(-2/2 - u)(-2/2 + u) = -3
1 - u^2 = -3
u^2 = 4
u = +/-2
then find the values for x_1 amd x_2
x_1 = - b/2 - u
=-2/2 - 2
= -1 - 2
x_1 = -3
x_2 = -b/2 + u
=-2/2 + 2
=-1 + 2
x_2 = 1